Familial scleroderma. - Milano, A. (European Journal of Pediatric Dermatology, 2012)
Case 1. An 8-year-old girl presented for 3 months angioma-like lesions of the left cheek. The physical examination, besides the angioma-like lesions of the left parotid and mandibular region put in evidence two whitish, scleroderma lesions on the left mandibular (Fig. 1, arrows) and palpebral region. When we talked about angioma-like scleroderma, the mother showed her hands (Fig. 1) informing us of being affected by systemic sclerosis. Case 2. A 9-year-old girl presented for six months asymptomatic erythematous lesions of the left abdomen and side (Fig. 2). The physical examination showed barely perceptible atrophy, leading us to diagnose superficial scleroderma. After the diagnosis to her daughter the mother showed us a hyperpigmented and sclerotic plaque of the left lumbar region (Fig. 2), which led us to the diagnosis of scleroderma.